2015
DOI: 10.1016/j.sleep.2015.02.061
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality from obstructive sleep apnea in male and female patients with and without continuous positive airway pressure treatment: A registry study with 10 years of follow-up

Abstract: Background: More information is needed about the effect on mortality of continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea (OSA), especially in women. Methods:We employed a historical cohort study design, using data from 25,389 patients with a diagnosis of OSA selected from the Danish National Patient Registry for the period 1999-2009. We used Cox proportional hazard function to evaluate the all-cause mortality from OSA in middle-aged and elderly males and females who were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Further recent epidemiological reports with several hundred elderly subjects combined mainly contain data about the link between SDB in the elderly and a rapid cognitive decline [144][145][146]. One very recent article encompassing a registry of of >25 000 OSA patients in Denmark followed up over >10 years presented age-stratified data comparing the survival rate of PAP users to OSA patients who were, for various reasons, not treated with PAP [147]. The protective effect of PAP appeared particularly strong in older men >60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Further recent epidemiological reports with several hundred elderly subjects combined mainly contain data about the link between SDB in the elderly and a rapid cognitive decline [144][145][146]. One very recent article encompassing a registry of of >25 000 OSA patients in Denmark followed up over >10 years presented age-stratified data comparing the survival rate of PAP users to OSA patients who were, for various reasons, not treated with PAP [147]. The protective effect of PAP appeared particularly strong in older men >60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Jennum et al [52], who reported a registry study with 10 years of follow-up, found that CPAP therapy was associated with reduced all-cause mortality in middle-aged and elderly men, but no significant effect was found in women. They showed that women with OSA had lower mortality rates than men, irrespective of whether or not they received CPAP treatment.…”
Section: Obstructive Sleep Apnea (Osa)mentioning
confidence: 99%
“…Previous cohort studies have shown female patients to have a lower morbidity and mortality rate than males [3,4]. CPAP has been shown to improve survival in male patients [5], but less so in females [4].…”
Section: Introductionmentioning
confidence: 98%
“…Severe obstructive sleep apnoea has been associated with a 1.9-times increased risk in all-cause mortality and 2.65-times increased risk of cardiovascular mortality [2]. Previous cohort studies have shown female patients to have a lower morbidity and mortality rate than males [3,4]. CPAP has been shown to improve survival in male patients [5], but less so in females [4].…”
Section: Introductionmentioning
confidence: 99%